2022
DOI: 10.1186/s12889-022-12960-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and socio-demographic correlates of hypertension among women (15–49 years) in Lesotho: a descriptive analysis

Abstract: Background Hypertensive disorders are among the leading conditions for severe maternal morbidity across all regions and have a major impact on health care costs. This study aimed to identify the prevalence and its associated socio-demographic correlates of hypertension among women of the reproductive ages in Lesotho. Methods The study used the Lesotho Demographic and Health Survey (2014 LDHS) data set. A total of 3353 women of childbearing age (15–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Also, having unimproved toilet type in households was associated with increased SBP while using primitive fuel for cooking in households was associated with decreased DBP. Our finding that older ages was associated with increased SBP and DBP is not surprising because generally the older the age, the higher the chance of one developing hypertension and this is consistent with previous studies that found that high blood pressure increase with an increasing age [12,13,18,[29][30][31]. Consistent with previous studies that reported increase in hypertension prevalence among those who are obese [12,13,30,31], being obese was associated with increased SBP and DBP PLOS GLOBAL PUBLIC HEALTH in this study.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 4 more Smart Citations
“…Also, having unimproved toilet type in households was associated with increased SBP while using primitive fuel for cooking in households was associated with decreased DBP. Our finding that older ages was associated with increased SBP and DBP is not surprising because generally the older the age, the higher the chance of one developing hypertension and this is consistent with previous studies that found that high blood pressure increase with an increasing age [12,13,18,[29][30][31]. Consistent with previous studies that reported increase in hypertension prevalence among those who are obese [12,13,30,31], being obese was associated with increased SBP and DBP PLOS GLOBAL PUBLIC HEALTH in this study.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…Thus, Upper West and Greater Accra regions consistently recorded the lowest and the highest hypertension prevalence respectively, on all the four outcome measures. The national prevalence based on SBP and DBP, and a combined (i.e., SBP and/or DBP) prevalence among this group of women aged 15–49 in Ghana was lower than the combined prevalence of 20% reported for women aged 15–49 years in Lesotho [ 18 ], 41.4% in Guatemala [ 26 ], and 33.8% in Ghana [ 12 ].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations